Pengaruh Metode Contextual Teaching and Learning untuk Meningkatkan Kompetensi pada Materi Realitas Sosial (Studi Kasus : Kelas X MAN 1 Jepara) - Iswati, Iswati; Sukarman, Sukarman; Faqih, Abdulloh (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This research shows that the Contextual Teaching and Learning (CTL) learning model has a positive impact in increasing students' interest and learning outcomes in the Sociology subject in Phase E. CTL allows teachers to connect academic concepts with real life situations, thereby creating a more relevant and relevant learning experience. meaningful for students. This method has proven effective in increasing student engagement and deepening their understanding of the subject matter. However, implementing CTL requires adequate training for teachers to be able to create a learning environment that is inspiring and meets students' needs. Apart from that, developing contextual and relevant teaching materials is an important aspect to support learning that is adaptive to students' needs. This research also opens up opportunities to apply CTL to various subjects and different grade levels, as well as exploring the best strategies to optimize learning outcomes. With these findings, the research makes a practical contribution to teachers and schools, helping to create more innovative and responsive learning approaches. Furthermore, this research also provides a scientific basis for developing curriculum and educational policies that support the wider implementation of contextual learning in the future. This shows that the application of CTL not only supports the achievement of academic goals, but also equips students with critical thinking abilities and relevant life skills.